Nuclear Osteopontin Is a Marker of Advanced Heart Failure and Cardiac Allograft Vasculopathy: Evidence From Transplant and Retransplant Hearts - Irion, Camila Iansen; Dunkley, Julian C.; John-Williams, Krista; Condor Capcha, José Manuel; Shehadeh, Serene A.; Pinto, Andre; Loebe, Matthias; Webster, Keith A.; Brozzi, Nicolas A.; Shehadeh, Lina A. (Frontiers in Physiology, 2020)
Background: Heart transplant is the gold standard therapy for patients with advanced heart failure. Over 5,500 heart transplants are performed every year worldwide. Cardiac allograft vasculopathy (CAV), is a common complication post-heart transplant which reduces survival and often necessitates heart retransplantation. Post-transplant follow-up requires serial coronary angiography and endomyocardial biopsy (EMB) for CAV and allograft rejection screening respectively; both of which are invasive procedures. This study aims to determine whether Osteopontin (OPN) protein, a fibrosis marker often present in chronic heart disease, represents a novel biomarker for CAV. Methods: Expression of OPN was analyzed in cardiac tissue obtained from patients undergoing heart retransplantation using immunofluorescence imaging (n=20). Tissues from native explanted hearts and 3 serial follow-up EMB samples of transplanted hearts were also analyzed in 5 of these patients. Results: 15/20 patients undergoing retransplantation had CAV. 13/15 patients with CAV expressed nuclear OPN. 5/5 patients with multiple tissue samples expressed nuclear OPN in both 1st and 2nd explanted hearts while 0/5 expressed nuclear OPN in any of the follow-up EMBs. 4/5 of these patients had an initial diagnosis of dilated cardiomyopathy (DCM). Conclusion: Nuclear localization of OPN in cardiomyocytes of patients with CAV was evident at the time of cardiac retransplant as well as in patients with DCM at the time of the 1st transplant. The results implicate nuclear OPN as a novel biomarker for severe CAV and DCM.